The Moderating Effect Satisfaction has on Turnover Intentions and Organizational Citizenship Behavior - Weeks, Kelly; Sen, Kanir (Journal of Management Policy and Practice, 2019)
This exploration contemplates the notion that there are moderating factors that affect employee turnover intentions when analyzing Organizational Citizenship Behavior (OCB). This study then investigates and analyzes the role satisfaction plays as a possible moderator between turnover and OCB. It is this paper’s contention that in order to be able to forecast or minimize employee turnover, one must understand all the variables and interactions. So, to that effect, this paper provides results from a large-scale survey and gives insight into the possible relationships. It further addresses current and future needs it this area.